2019
DOI: 10.1021/jacs.9b05558
|View full text |Cite
|
Sign up to set email alerts
|

Meltable Mixed-Linker Zeolitic Imidazolate Frameworks and Their Microporous Glasses: From Melting Point Engineering to Selective Hydrocarbon Sorption

Abstract: Porous glasses from metal−organic frameworks (MOFs) represent a new class of functional inorganic−organic materials, which have been proposed for applications ranging from solid electrolytes to radioactive waste storage. So far, just a few zeolitic imidazolate frameworks (ZIFs), a subset of MOFs, have been reported to melt and the structural and compositional requirements for MOF melting and glass formation are poorly understood. Here, we show how the melting point of the prototypical ZIF-4/ZIF-62(M) framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
251
1
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(283 citation statements)
references
References 71 publications
19
251
1
12
Order By: Relevance
“…The pore size radius of ZIF‐62 glass (3.16 Å) was much larger than that of crystalline ZIF‐62 (2.66 Å). The result was in line with the previous report …”
Section: Figuresupporting
confidence: 94%
See 1 more Smart Citation
“…The pore size radius of ZIF‐62 glass (3.16 Å) was much larger than that of crystalline ZIF‐62 (2.66 Å). The result was in line with the previous report …”
Section: Figuresupporting
confidence: 94%
“…The ZIF‐62 crystals melted at 434 °C, consistent with prior observations . The melting temperature ( T m ) of ZIF‐62 crystals can be engineered by adjusting the molar ratio of Im to Bim . Thermogravimetric (TG) analysis (Figure S1) exhibited no obvious weight loss during the whole melting process, suggesting the excellent thermal stability of ZIF‐62.…”
Section: Figuresupporting
confidence: 84%
“…As the bIm ligands occupy much more space than the Im ligands, the porosity decreases with the increase of the bIm ligands, which is consistent with the experiments in ref. 35. And the glass network is still well preserved as shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
“…In ref. 35, Frentzel-Beyme et al found that there was a minor loss of porosity upon melting and forming a-ZIF-62 glasses. And the gas (n-butane, propane and propylene) sorption isotherms decrease with increasing bIm concentration, which indicates that the pore aperture size also reduces.…”
Section: Resultsmentioning
confidence: 99%
“…The central ions and the organic ligand or ligand combination play the main role in the assembly of MOFs. Porous MOFs can capture guest molecules and show potential applications for storage, separation and purification (Kubas 2007;Ye et al, 2019;Frentzel-Beyme et al, 2019). Low-dimensional MOFs can construct high-dimensional supramolecular architectures via hydrogen-bonding interactions (Liu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%